2018
DOI: 10.1002/adma.201704908
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Induced Reversible Control of Ferroelectric Polarization in BiFeO3

Abstract: Manipulation of ferroic order parameters, namely (anti-)ferromagnetic, ferroelectric, and ferroelastic, by light at room temperature is a fascinating topic in modern solid-state physics due to potential cross-fertilization in research fields that are largely decoupled. Here, full optical control, that is, reversible switching, of the ferroelectric/ferroelastic domains in BiFeO thin films at room temperature by the mediation of the tip-enhanced photovoltaic effect is demonstrated. The enhanced short-circuit pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
125
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(127 citation statements)
references
References 28 publications
2
125
0
Order By: Relevance
“…Significantly, we observed a switchable photocurrent for this two‐terminal α‐In 2 Se 3 memristor (Figure g), which provides another degree of freedom for using light to control the conducting path of the device and further construct nonvolatile photomemories. The photocurrent in ferroelectric α‐In 2 Se 3 memristor arises from the separation of photogenerated electron–hole pairs, rather than noncentrosymmetry induced bulk photovoltaic effect in conventional oxide ferroelectrics . It is reported that the incident‐light‐induced thermal effect in α‐In 2 Se 3 can be ignored due to the tiny temperature gradient (0.1 K) under a large power density of 100 W cm −2 .…”
mentioning
confidence: 63%
“…Significantly, we observed a switchable photocurrent for this two‐terminal α‐In 2 Se 3 memristor (Figure g), which provides another degree of freedom for using light to control the conducting path of the device and further construct nonvolatile photomemories. The photocurrent in ferroelectric α‐In 2 Se 3 memristor arises from the separation of photogenerated electron–hole pairs, rather than noncentrosymmetry induced bulk photovoltaic effect in conventional oxide ferroelectrics . It is reported that the incident‐light‐induced thermal effect in α‐In 2 Se 3 can be ignored due to the tiny temperature gradient (0.1 K) under a large power density of 100 W cm −2 .…”
mentioning
confidence: 63%
“…Importantly, it has been reported that a change in short‐circuit current can cause charge injection leading to the tuning of the coercive field . The maximum electric field associated with induced current injection can be calculated using the following equationEmax=0.4InormalSCπθ με0 εr1/21r1/2…”
Section: Resultsmentioning
confidence: 99%
“…Several non‐centrosymmetric perovskites are also ferroelectric in nature. “A ferroelectric material is a material that exhibits, over some range of temperature, a spontaneous electric polarization that can be reversed or reoriented by application of an electric field (as illustrated in Figure b,c).” The spontaneous polarization of several ferroelectrics can also be reversibly switched by application of stress, uniform heating/cooling, or light . The phenomena of achieving a change in polarization by means of uniform heating or cooling is known as the “pyroelectric effect” while a change in polarization by exposure to light and stress is termed as “photoferroic effect” and “piezoelectric effect,” respectively.…”
Section: Introductionmentioning
confidence: 99%